Incidencia de las representaciones sociales de Machachi en la identidad cultural de los rockeros. - Patiño Quillupangui, Franklin Eduardo (2018)
The problematic related to the influence of the social representations of the population of Machachi on the rockers of the city, requires a meticulous analysis, because this group generates signs that have different meanings depending on the perception that each individual has, this allows the formation of different social representations, this subject has been insufficiently studied from communication area. At this sense, this project aimed to determine the extent how the social representations of Machachi rockers affect the construction of their cultural identity. The methodological strategy that was implemented had a qualitative approach, through the technique of the focal group, to obtain the information was carried out in focus groups, in group one, the participation of adults between 30 and 60 years old who reside from the Machachi city, while in group two, people who belong to the culture and rock subcultures participate, mostly young people between 25 and 40 years old. Among the main results are the social representations about people who belong to the rock culture, are marked by social stigmas determined as countercultural. In addition, it was possible to know how the perception of the individuals residing in the city influences the rocker. Among the main conclusions is that the rock culture of the Machachi city is differentiated by ideologies, customs and actions, consequently it is classified as a negative entity for the rest of society, in turn, the perception of adults of Machachi, it influences the formation of the cultural identity of the rocker, so we will have to make changes in the actors before people who are not part of the rock culture.